THE STATE OF FORMATION OF THE PROVISION OF THE OF INVESTMENT SECURITY SYSTEM OF UKRAINE - Мороз , Максим (Socio-economic relations in the digital society, 2019)
The significance of the formation of a system of providing investment security for ensuring the vital activity of the state has been determined. The author’s definition of the system of providing investment security has been given. The components of such a system have been singled out. The reasons for its absence in Ukraine have been determined. The state of scientific support for the formation of such a system and specific gaps in this area have been critically evaluated; a regulatory framework, regulating investment activity and ensuring investment security. The organizational, methodical, accounting, statistical and informational-analytical aspects of such formation have been described. It has been emphasized, that there are significant shortcomings in the estimation of the total volume of investments in Ukraine, the inflow of foreign investments and the outflow of domestic and foreign capital, the total volume of bank investment loans, the geographical origin of foreign capital in Ukraine, management of investment projects, state regulation of investment activity. The factors of low investment potential of Ukraine have been revealed. Destimulators have been found to raise the level of investment security in Ukraine.